Wo nur ist Sauls Kopf geblieben? Überlegungen zu ISam 31 - Hunziker-Rodewald, Regine (2004)
A comparison between the narrative of Saul’s death in ISam 31 and the Assyrianrepresentation of the death of Te’umman, the king of Elam displays an essentialdifference: in ISam 31 it is the beheaded body of Saul that is focused on, incontrast with the relief from Niniveh where the head-trophy occupies the centrestage. This is related to the fact that in the first case the narrative is told fromthe perspective of the unsuccessful party, while the second takes the perspectiveof the victor. This variation is found in all different versions of the narratives,in the Assyrian sources for the death of Te’umman and the ancient versions and Josephus for the death of Saul – with the exception of IChr 10! Chrconcentrates on the head-trophy and in doing so not only displays the perspectiveof the victor but also noticeably glorifies David, whereas it casts a grim lighton the portrayal of Saul.Finally, the Wirkungsgeschichte of the narration elucidates the value of thenarrative variations for the interpretation of the story: Max Zweig gives a faceto the dead Saul in his drama Saul (1944). This portrayal contrasts so stronglywith the representation of the dead Saul in the Bible as a beheaded body only(ISam 31) or as a head-trophy (IChr 10) that it makes one realise even morehow the two literary variations steer the reader in one or the other direction of interpretation.
Literaturverzeichnis: Seite 297-300
Keywords: Saul -- Israel, König; Bibel; Tod